1998
DOI: 10.1095/biolreprod59.5.1108
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Oxytocin Pretreatment Inhibits Adenylyl Cyclase Activity in Cultured Rat Myometrial Cells1

Abstract: To determine whether chronic oxytocin pretreatment inhibits adenylyl cyclase, we compared adenylyl cyclase activity in membranes prepared from cultured, immortalized rat myometrial cells that were untreated or pretreated for 24 h with oxytocin. Chronic oxytocin pretreatment (1 x 10(-5) M for 24 h) attenuated basal, guanosine triphosphate (1 x 10(-5) M)-, isoproterenol (1 x 10(-4) M)-, forskolin (1 x 10(-5) M)-, MnCl2 (20 mM)- or NaF (1 x 10(-2) M)-stimulated adenylyl cyclase activity by 27 +/- 5% to 39 +/- 11%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…The current study also agrees with a recently published study from our laboratory using myometrial cells demonstrating that chronic treatment of cultured rat myometrial cells with either oxytocin or phenylephrine (both coupled to G q ␣) resulted in decreased adenylyl cyclase activity in response to GTP, isoproterenol, NaF, MnCl 2 , or forskolin (suggesting cross-regulation at the level of adenylyl cyclase) by a mechanism that was blocked by prior depletion of PKC by prolonged phorbol ester treatment (19). Thus these studies in a variety of cell lines coupled with the results of the present study suggest that G q ␣/PKC activation potentially cross-regulates several levels of the receptor-G s ␣adenylyl cyclase cascade, but the present study is the first study to demonstrate a downregulation of adenylyl cyclase protein.…”
Section: Discussionsupporting
confidence: 92%
“…The current study also agrees with a recently published study from our laboratory using myometrial cells demonstrating that chronic treatment of cultured rat myometrial cells with either oxytocin or phenylephrine (both coupled to G q ␣) resulted in decreased adenylyl cyclase activity in response to GTP, isoproterenol, NaF, MnCl 2 , or forskolin (suggesting cross-regulation at the level of adenylyl cyclase) by a mechanism that was blocked by prior depletion of PKC by prolonged phorbol ester treatment (19). Thus these studies in a variety of cell lines coupled with the results of the present study suggest that G q ␣/PKC activation potentially cross-regulates several levels of the receptor-G s ␣adenylyl cyclase cascade, but the present study is the first study to demonstrate a downregulation of adenylyl cyclase protein.…”
Section: Discussionsupporting
confidence: 92%
“…Although isoproterenol stimulated AC activity in the presence of GTP, the resultant increase did not surmount AC activity in the presence of GTP alone. This low responsiveness of AC to isoproterenol may indicate desensitization and uncoupling of the ␤-adrenergic receptor at term [34] and has also been observed in human myometrial tissue at term [35] and in rabbit [36] and rat myometrial cells [37]. It was recently demonstrated that ␤-adrenergic receptors, G proteins, and AC are colocalized in caveolar microdomains of the membrane and that this colocalization enhances coupling efficiency [38].…”
Section: Discussionmentioning
confidence: 68%
“…Stimulation of the G q ‐mediated pathway produces inositol triphosphate and increases the activity of protein kinase C 17 . Lindeman et al 18 . reported that activation of G q desensitizes the pathway leading to adenylyl cyclase stimulation and localized the effect to protein kinase C. The oxytocin‐induced inhibition of adenylyl cyclase activity via PKC was also observed during the direct stimulation of the β‐adrenergic receptor coupled to G s , however the site of desensitization was postulated to be distal to the G s ‐protein coupled receptor 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Oxytocin receptors in myometrium are coupled to the Gq 15 and Gi 16 proteins. Stimulation of the Gq-mediated pathway produces inositol triphosphate and increases the activity of protein kinase C. 17 Lindeman et al 18 reported that activation of Gq desensitizes the pathway leading to adenylyl cyclase stimulation and localized the effect to protein kinase C. The oxytocin-induced inhibition of adenylyl cyclase activity via PKC was also observed during the direct stimulation of the b-adrenergic receptor coupled to Gs, however the site of desensitization was postulated to be distal to the Gs-protein coupled receptor. 18 Stimulation of the latter oxytocin receptor via linkage to Gi, that directly inhibits adenylyl cyclase and therefore inhibits relaxation, is also adding to the decrease in adenylyl cyclase activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation